2019
DOI: 10.1002/mame.201900323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blending Procedure on Tensile and Degradation Properties of Toughened Biodegradable Poly(lactic acid) Blend with Poly(trimethylene terephthalate) and Reactive Compatibilizer

Abstract: This research focuses on brittleness improvement of biodegradable poly(lactic acid) (PLA) by reactive melt blending with poly(trimethylene terephthalate) (PTT). First, PLA is simultaneously blended with PTT and a reactive compatibilizer, poly(ethylene‐co‐glycidyl methacrylate) (PEGMA), (one‐step blending procedure). In the PLA/PTT/PEGMA blend, PEGMA mainly disperses in the PLA matrix phase, and the blend shows unimproved tensile properties. To increase the reaction between PTT and PEGMA, PEGMA is sequentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…To overcome the shortcomings of PLA, various organic and inorganic fillers have been introduced as reinforcing materials to develop PLA‐dominant blends and composites. [ 5,11–23 ] The stereocomplexation ability of PLA isomers has been also proposed as an effective method for enhancing the thermal and mechanical properties. [ 24,25 ] Some researchers have explored the potential of blending PLA with conventional polymers to improve performance and lower prices by investigating the blends in terms of miscibility, morphology, thermal, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the shortcomings of PLA, various organic and inorganic fillers have been introduced as reinforcing materials to develop PLA‐dominant blends and composites. [ 5,11–23 ] The stereocomplexation ability of PLA isomers has been also proposed as an effective method for enhancing the thermal and mechanical properties. [ 24,25 ] Some researchers have explored the potential of blending PLA with conventional polymers to improve performance and lower prices by investigating the blends in terms of miscibility, morphology, thermal, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more biodegradable polymers were used to toughen PLA. [26][27][28][29][30][31][32][33][34] Ojijo Vincent et al prepared PLA/PBSA blends. 29 For a blend containing 40 wt% PBSA and 0.6 wt% chain extender, the impact strength of PLA was increased from 4.6 to 38.4 kJ/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more biodegradable polymers were used to toughen PLA 26‐34 . Ojijo Vincent et al prepared PLA/PBSA blends 29 .…”
Section: Introductionmentioning
confidence: 99%
“…For preparation of the composite material, two-step blending was performed on the basis of our previous research . In that study, toughening of PLA by blending with PTT was performed using the reactive compatibilizer of PEGMA.…”
Section: Methodsmentioning
confidence: 99%
“…To prepare the interfacial localization of the modified filler in cocontinuous immiscible polymer blend, a blend of biobased poly­(lactic acid) (PLA) with a partially biobased aromatic polyester, poly­(trimethylene terephthalate) (PTT), was adopted based on our previous studies. , Previous results have shown that the tensile properties of the PLA/PTT blend have been significantly enhanced by improved interfacial adhesion between PLA and PTT using a reactive compatibilizer, poly­(ethylene- co -glycidyl methacrylate) (PEGMA). The epoxy group of the glycidyl methacrylate (GMA) part in the PEGMA reacted with the end groups of both PLA and PTT, and then, PEGMA was located at the interface between PLA and PTT.…”
Section: Introductionmentioning
confidence: 99%